Pemenuhan Hak Anak Dalam Menunjang Pemasyarakatan Yang Mengedepankan Hak Asasi Manusia - Maskur Hidayat; Ali Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Child protection is an integral part of human rights. Every child has the right to live, develop, and be protected from all forms of discrimination, violence, and exploitation. Special protection is afforded to children involved in the justice system, including those engaged in legal violations, children who are victims of crimes, and children who serve as witnesses in legal proceedings. The research method employed is a normative juridical approach, and the research methodology used is a descriptive-analytical approach to elucidate the situation and information related to the fulfillment of children's rights within correctional institutions. Therefore, to fulfill children's rights in accordance with Law Number 35 of 2014 concerning child protection, correctional facilities must provide special treatment for children.